2021
DOI: 10.1111/jbi.14053
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of wing length and melanin‐based coloration in insular populations of a cosmopolitan raptor

Abstract: Aim Insular populations face different conditions than those living on continents, thus, resulting in the evolution of typical insular phenotypes, like smaller body sizes or reduced colourations. However, the generality of the so‐called “island rule” has been questioned, and intraspecific analyses on the effects of insularity on cosmopolitan species are lacking. Here, we tested the predictions of the island rule in the cosmopolitan common barn owl group. Location World. Taxon Barn owl species complex. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 82 publications
2
21
0
1
Order By: Relevance
“…Therefore, it appears the white insular morph can be most parsimoniously explained by relaxation or absence of selective pressure in contrast to the mainland. Such a pattern is actually common among insular birds which, due to relaxed selection, tend to display less colourful plumage than their mainland counterparts (Doutrelant et al, 2016;Grant, 1965), as also observed in the barn owl worldwide (Romano, Séchaud, & Roulin, 2021). This early history of colonisation of the British Isles inferred here from whole-genome sequences and supported by SDM projections on past climatic features is apparently unique among terrestrial vertebrates, but it is far from the first to deviate from the most common colonisation route over Doggerland (e.g.…”
Section: Colonisation Of the British Islesmentioning
confidence: 62%
“…Therefore, it appears the white insular morph can be most parsimoniously explained by relaxation or absence of selective pressure in contrast to the mainland. Such a pattern is actually common among insular birds which, due to relaxed selection, tend to display less colourful plumage than their mainland counterparts (Doutrelant et al, 2016;Grant, 1965), as also observed in the barn owl worldwide (Romano, Séchaud, & Roulin, 2021). This early history of colonisation of the British Isles inferred here from whole-genome sequences and supported by SDM projections on past climatic features is apparently unique among terrestrial vertebrates, but it is far from the first to deviate from the most common colonisation route over Doggerland (e.g.…”
Section: Colonisation Of the British Islesmentioning
confidence: 62%
“…Therefore, it appears the white insular morph can be parsimoniously explained by relaxation or absence of selective pressure in contrast to the mainland. Such a pattern is actually common among insular birds which, due to relaxed selection, tend to display less colourful plumage than their mainland counterparts (Doutrelant et al, 2016 ; Grant, 1965 ), as also observed in the barn owl worldwide (Romano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 77%
“…This classification is based on its smaller size and even on colouration pattern, although the latter is contested by ornithologists and inconsistent with reported phenotypical measurements (Burri et al 2016). The reduction in size is actually a common pattern in insular barn owls (Romano et al 2021), and could be an adaptation to nesting in very small cavities (i.e. cracks in lava walls) and/or to better navigate the strong winds in the eastern islands (Siverio 2007).…”
Section: Discussionmentioning
confidence: 99%